User Experience Pengguna Learning Management System Seal Menggunakan Metode Heart Metrics - Krisya Khoiriyah; Arista Pratama; Asif Faroqi (STMIK Budi Darma, 2023)
The SEAL Learning Management System (LMS SEAL) is an online learning platform owned by the SEAL independen study program which has the function of bridging communication between mentors and students during the independent study program. This Learning Management System was created and developed with the aim of making it easier for SEAL independent study students to view material provided by SEAL mentors so that they can be studied anytime and anywhere. The SEAL LMS has not been utilized properly and optimally by SEAL independent study participants during the program, therefore this research was conducted using the HEART Framework to measure user experience (UX) originating from SEAL independent study participants. In this study all HEART variables were used, namely Happiness, Engagement, Adoption, Retention, Task Success to find appropriate results for consideration in the development of LMS SEAL. The data collection process was carried out by distributing questionnaires in the form of g-forms which were distributed to independent study participants batch 1 and batch 2 with a total of 120 students. All results from the questionnaire obtained were tested for validity and reliability tests and confirmed that they met valid and reliable criteria for all items. This study has a Goal-Signal-Metric set that determines the success rate of all variables. User experience based on the HEART method obtained the results of the Happiness variable of 77.10%, Engagement of 77.60%, Adoption of 79.50%, Retention of 80.70%, and Task Success of 77.20%. The results showed that only one variable met the Goal-Signal-Metrics Set which meant that LMS SEALs had to be further developed to improve the quality of LMS SEAL